Germany, France and Postwar Democratic Capitalism: Expert Rule - François Godard (Routledge, 2024)
This book concentrates on the political economies of Germany and France in the period spanning between the end of the Second World War and the 1970s, with a subsequent consideration of Italy and Britain as 'shadow cases'. European postwar accounts have never reconciled the thwarting of widespread aspirations to socialism, and the twin feat of equalitarian growth and institutional stability. This success is precisely due to achieving the reconciliation of democracy and economic management, the yearning for collective control over social and material outcomes that was tragically aborted in the interwar period, and fed 1945 expectations. Germany, in 1948–49, and France, in 1958, carried radical institutional and policy reforms with much more in common than previously realised. Under the recast republics, social groups were steered towards support for modernisation – by the state, not through a mythical settlement. Consensus was built for trade and low inflation as vectors for higher productivity. State capacity was lifted by leadership in ideas, executive branch accountability to voters, and technocratic agencies. British and Italian underperformances reveal the countries' uneasiness with the compact. Once understood, the convergence of productivism and democracy in the European regulatory state provides a new narrative – especially relevant today – of experts taming populists.
Keywords: 330; Marshall Plan; Fifth Republic; Postwar Democracy; Cold War; Willi Brandt; Charles de Gaulle; End of Colonialism